Abdominal cystic lymphangiomas in pediatric cases - Ali Farbod; Peyman Virani; Fatemeh Shohratifar; Mahshid Dehghan; Aisan Akhgari (Elsevier, 2022)
Mesenteric cystic lymphangiomas are benign but rare neoplasms, primarily seen in children. Among internal organs, these masses are commonly found in the ileal mesentery. In this case series, we presented nine pediatric patients with abdominal lymphangiomas admitted to the surgery ward during 2010 and 2020, of which 6 were boys and three girls. Symptoms varied from abdominal distention to chronic and acute abdominal pain, anorexia and vomiting, and a scrotal mass in our patients. Considering various presentations of these patients and possible critical complications, surgeons need to have lymphatic malformations in mind as a differential diagnosis in such cases to improve the outcome.